2022
DOI: 10.1101/2022.10.21.513200
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systems approach evaluating the impact of SARS-CoV-2 variant of concern mutations on CD8+ T cell responses

Abstract: T cell recognition of SARS-CoV-2 antigens after vaccination and/or natural infection has played a central role in resolving SARS-CoV-2 infections and generating adaptive immune memory. However, the clinical impact of SARS-CoV-2-specific T cell responses is variable and the mechanisms underlying T cell interaction with target antigens are not fully understood. This is especially true given the virus’ rapid evolution, which leads to new variants with immune escape capacity. In this study, we used the Omicron var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…We showed that the out-of-distribution detection module is well-suited for the 'needle in a haystack' problem by identifying those predicted negative with low confidence. In another study, we used TRAP to investigate the immune escape potential of SARS-CoV-2 variants 64 . By combining TRAP with in silico mutagenesis, we evaluated the extent to which all possible theoretical single point mutations can give rise to variants of concern and be detrimental to T-cell immunity.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the out-of-distribution detection module is well-suited for the 'needle in a haystack' problem by identifying those predicted negative with low confidence. In another study, we used TRAP to investigate the immune escape potential of SARS-CoV-2 variants 64 . By combining TRAP with in silico mutagenesis, we evaluated the extent to which all possible theoretical single point mutations can give rise to variants of concern and be detrimental to T-cell immunity.…”
Section: Discussionmentioning
confidence: 99%